A new agent of mycobacterial lymphadenitis in children: Mycobacterium heidelbergense sp. nov - Haas, Walter; Butler, W. R.; Kirschner, P.; Plikaytis, B. B.; Coyle, M. B.; Amthor, Beate; Steigerwalt, A. G.; Brenner, D. J.; Salfinger, M.; Crawford, J. T.; Böttger, E. C.; Bremer, Hans J. (Journal of clinical microbiology, 1997)
Nontuberculous mycobacterial lymphadenitis presents an increasing clinical problem in immunocompetent young children. A slowly growing, nonphotochromogenic mycobacterium was recovered twice (isolates 2553/91 and 2554/91) from the lymphatic tissue of a child with recurrent cervical lymphadenitis. It could be differentiated biochemically from described Mycobacterium species, although it most closely resembled Mycobacterium malmoense by thin-layer chromatography and high-performance liquid chromatography of mycolic acids. A striking characteristic of the isolate was its high degree of susceptibility to antituberculous drugs in vitro, including isoniazid. Direct determination of the 16S rRNA gene sequence revealed a unique sequence and positioned the strain phylogenetically on a branch separate from M. malmoense within a group of slowly growing mycobacteria that show a high degree of similarity to M. simiae at the 16S rRNA gene level. Despite 99.6% sequence identity with M. simiae at the 16S rRNA gene level, DNA-DNA hybridization studies (hydroxyapatite method) demonstrated DNA relatedness of less than 40%. We conclude that this organism is a new species for which we propose the name M. heidelbergense. A culture of the type strain, strain 2554/91, has been deposited in the American Type Culture Collection as strain ATCC 51253.
Gesehen am 20.06.2024